Dialogue summary: Improving access to mental health services for immigrant, refugee, and asylum seeker children, youth and their families in Canada - Ali, A; Bain, T; Moat, KA; Gauvin, Francois-Pierre; Lavis, JN (My University, 2023)
A thematic summary of what was learned from the stakeholder dialogue on improving access to mental health services for immigrant, refugee, and asylum seeker children, youth and their families in Canada, about the problem (and its causes), elements of a potentially comprehensive approach for addressing it, key implementation considerations, and possible next steps.
Keywords: access; mental health services; immigrant; asylum seeker; children; youth; Canada